2004
DOI: 10.1021/jf0306845
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrotomatine and α-Tomatine Content in Tomato Fruits and Vegetative Plant Tissues

Abstract: Tomato plants (Lycopersicon esculentum) synthesize the glycoalkaloids dehydrotomatine and alpha-tomatine, possibly as a defense against bacteria, fungi, viruses, and insects. We used a high-performance liquid chromatography method with UV detection at 208 nm for the analysis of these compounds in various tissues. An Inertsil ODS-2 column with a mobile phase of acetonitrile/20 mM KH2PO4 (24/76, v/v) afforded good separation of the two glycoalkaloids in mini-tomato extracts, fruit harvested at different stages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 29 publications
(38 reference statements)
6
91
0
2
Order By: Relevance
“…They suggested that the low oral toxicity of tomatine might be due to its ability of forming an insoluble complex with cholesterol in vivo which can then be eliminated through feces. Kozukue et al (2004) have suggested that biosynthesis/degradation of dehydrotomatine and -tomatine may be under distinct genetic control in the leaves of tomato plants. In this study, the contents of tomatine and tomatidine in the 50 tomato accessions were measured (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the low oral toxicity of tomatine might be due to its ability of forming an insoluble complex with cholesterol in vivo which can then be eliminated through feces. Kozukue et al (2004) have suggested that biosynthesis/degradation of dehydrotomatine and -tomatine may be under distinct genetic control in the leaves of tomato plants. In this study, the contents of tomatine and tomatidine in the 50 tomato accessions were measured (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…UDP-Gal was readily used as a donor, producing a novel product with a mass-to-charge ratio of 578 m/z ([M+H]), corresponding to galactosylated tomatidine (Figure 3). Dehydrotomatidine (414 m/z; Figure 3), identified in the tomatidine standard as a contaminant (Kozukue et al, 2004), was also galactosylated by GAME1 (product 576 m/z). UDP-Glc was also incorporated to some extent, however, not exceeding 5% of the Gal incorporation under identical concentrations and conditions.…”
Section: Functional Characterization Of the Game1 Recombinant Enzyme mentioning
confidence: 99%
“…A proposed pathway that represents the biosynthesis and metabolism of SAs during tomato fruit development (from the immature green to the RR stage) was generated based on previously published data (Friedman, 2002;Kozukue et al, 2004;Moco et al, 2007;Iijima et al, 2008Iijima et al, , 2009Mintz-Oron et al, 2008) and the data from this study ( Figure 6). …”
Section: Mg Fruit Of Game1i Plants Display Altered Levels Of Sasmentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge on the role of glycoalkaloids in pollen is scarce, but the different levels of glycoalkaloids observed in different stages of pollen development might be important to ensure an optimal defense against biotic attacks during plant reproduction. This idea would agree with the finding that the concentration of α-tomatin has been reported to be 2-fold higher in flowers than in leaves of tomato plants ( Kozukue et al 2004). …”
Section: Alkaloidssupporting
confidence: 91%